RETORT PROCESSED CHICKEN CURRY FROM BROILER AND DESI CHICKEN MEAT - P. Nalini; Robinson J.J Abraham; V. Appa Rao; R. Narendra Babu (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Low cost technologies for small and large scale production of meat products need to be developed to initiate and attract a large number of entrepreneurs to the processed meat industry. Retort pouches have advantages of shelf-stability, less weight, less storage space, ease of opening & preparation and storage without refrigeration.It has been shown that the use of retortable pouches for the thermo-processed foods is technical and commercially feasible. The present study was conducted to determine the suitable recipe formulation, retort processing temperature and shelf-life of the chicken curry with desi and broiler under ambient temperature (32+2°C)up to 3 months of period. Shelf-life studies included changes in microbiological, physicochemical composition and sensory characters.